Towards a Human Rights-Based Legal Framework for Genetic Technology in Indonesia - Marici, Alice Angela; Situmeang, Ampuan; Disemadi, Hari Sutra (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The lack of specific legal provisions addressing the misuse of genetic information in Indonesia raises critical concerns regarding potential violations of the right to privacy and genetic-based discrimination. This study aims to examine the extent to which Indonesia’s legal framework protects human rights in the era of genetic technology. Employing a normative legal research method, the study utilizes statutory and conceptual approaches to analyze relevant laws, including the 1945 Constitution, the Human Rights Law, and the Personal Data Protection Law. The findings reveal that while Indonesia’s existing legal framework provides foundational human rights protections, it fails to explicitly regulate genetic data as a distinct category requiring heightened safeguards. Key issues include the absence of mechanisms for informed consent, vague data governance, and a lack of explicit prohibitions on genetic discrimination. As genetic testing expands—particularly in health, research, and insurance sectors—the risk of rights violations becomes more imminent. The study recommends comprehensive reform through the creation of dedicated legislation, establishment of an independent oversight body, and adoption of progressive legal principles such as autonomy, non-discrimination, and precaution. Without such reforms, Indonesia risks falling behind in ethically and legally navigating genetic innovation while compromising constitutional human rights guarantees. Without such reforms, Indonesia risks falling behind in ethically and legally navigating genetic innovation while compromising constitutional human rights guarantees. [Kurangnya ketentuan hukum yang secara spesifik mengatur penyalahgunaan informasi genetik di Indonesia menimbulkan kekhawatiran serius terkait potensi pelanggaran hak atas privasi serta diskriminasi berbasis karakteristik genetik. Penelitian ini bertujuan untuk mengkaji sejauh mana kerangka hukum Indonesia melindungi HAM dalam era perkembangan teknologi genetik. Dengan menggunakan metode penelitian hukum normatif, studi ini menerapkan pendekatan perundang-undangan dan konseptual untuk menganalisis berbagai regulasi yang relevan, termasuk UUD NRI 1945, UU Hak Asasi Manusia, serta UU Pelindungan Data Pribadi. Temuan penelitian menunjukkan bahwa meskipun kerangka hukum Indonesia saat ini telah menyediakan perlindungan dasar terhadap hak asasi manusia, regulasi tersebut belum secara tegas mengatur data genetik sebagai kategori khusus yang memerlukan perlindungan lebih kuat. Beberapa isu utama yang ditemukan antara lain ketiadaan mekanisme persetujuan berdasarkan informasi (informed consent), ketidakjelasan tata kelola data, serta belum adanya larangan eksplisit terhadap diskriminasi genetik. Seiring dengan meluasnya penggunaan tes genetik- terutama dalam sektor kesehatan, penelitian, dan asuransi-risiko terjadinya pelanggaran hak semakin meningkat. Penelitian ini merekomendasikan dilakukannya reformasi hukum secara komprehensif melalui pembentukan regulasi khusus, pendirian lembaga pengawas independen, serta penerapan prinsip-prinsip hukum progresif seperti otonomi, non-diskriminasi, dan prinsip kehati-hatian. Tanpa adanya reformasi tersebut, Indonesia berisiko tertinggal dalam menghadapi inovasi genetik secara etis dan legal, sekaligus berpotensi mengorbankan jaminan hak konstitusional warga negara.